(untitled) (Analysis in Theory and Applications, 2013)
We consider for a fixed μ, the class of polynomials P_n,μ,s:={ P(z) =z^s(a_nz^n−s+ ^n-s_j=μa_n−jz^n−j−s); 1≤μ≤n−s} of degree n, having all zeros in |z|≤k, k≤1, with s-fold zeros at the origin. In this paper, we have obtained inequalities in the reverse direction for the above class of polynomials. Besides, extensions of some Turan-type inequalities for the polar derivative of polynomials have been considered.